Enzymatic synthesis of ascorbyl palmitate in ultrasound-assisted system: Process optimization and kinetic evaluation - Lerin L. A.; Feiten M. C.; Richetti A.; Toniazzo G.; Treichel H.; Mazutti M. A.; Vladimir Oliveira J.; Oestreicher E. G.; De Oliveira D. (Ultrasonics Sonochemistry, 2011)
This work is focused on the optimization of reaction parameters for the synthesis of ascorbyl palmitate catalyzed by Candida antarctica lipase in different organic solvents under ultrasound irradiation. The sequential strategy of experimental design proved to be useful in determining the optimal conditions for reaction conversion in tert-butanol system using Novozym 435 as catalyst. The optimum production was achieved at 70°C, ascorbic acid to palmitic acid molar ratio of 1:9, enzyme concentration of 5 wt% at 3 h of reaction, resulting in an ascorbyl palmitate conversion of about 27%. Reaction kinetics for ascorbyl palmitate production in ultrasound device showed that satisfactory reaction conversions (∼26%) could be achieved in short reaction times (2 h). The empirical kinetic model proposed is able to satisfactorily represent and predict the experimental data. © 2011 Elsevier B.V. All rights reserved.